A technical appraisal of solar photovoltaic-integrated single slope single basin solar still for simultaneous energy and water generation - S. Shanmugan; Karrar A. Hammoodi; T. Eswarlal; P. Selvaraju; Samir Bendoukha; Nabil Barhoumi; Mohamed Mansour; H.A. Refaey; M.C. Rao; Abdel-Hamid I. Mourad; Manabu Fujii; Ammar Elsheikh (Case Studies in Thermal Engineering, 2024)
In the contemporary era, the availability of energy and water stands as an essential foundation for human survival, with water's significance underscored by its role in shaping habitats. However, the modern world faces the pressing challenge of water scarcity, exacerbated by factors like air and water pollution, leading to ecological imbalances. Water, an indispensable resource for various daily human activities, necessitates the generation of freshwater. Simultaneously, the imperative of sustainable energy generation has taken precedence on the national agenda for growth. In this context, the integration of solar photovoltaic (PV) technology with solar stills emerges as the most viable solution. Within these integrated systems, electrical energy generated by solar PV is strategically employed to preheat inlet feeds, enhance air temperature, and optimize the evaporation and condensation processes within the solar still, thereby augmenting its overall performance. This study delves into the integration of solar PV collectors/systems with solar stills, distinguishing between thermal and electrical energy utilization in solar PV systems. The review underscores the pivotal role of solar PV integration in addressing critical issues of water scarcity and sustainable energy generation, contributing to the nation's growth.